Gastroprotective Effect of Quercetin and Misoprostol in Ethanol-Induced Gastric Ulcer in Rats - Ahmed, Zheen Aorahman (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study aimed to evaluate the possible synergistic gastroprotective activity of quercetin and misoprostol in gastric ulcers induced by ethanol in rats. Materials and Methods: Male Wister albino rats were allocated into 6 groups: Negative control, positive control, esomeprazole, quercetin, misoprostol, and a combination of quercetin and misoprostol. All the treatment groups except for the negative control were challenged with a single dose of ethanol (90%) after 14 days of treatment. The animals were euthanized 1 hour after ethanol administration, and the blood samples were collected and used for the measurement of catalase, GSH, LDH, and IL-6. The stomachs were immediately removed and used for the measurement of gastric ulcer index, lesion area, gastric volume, and pH. Finally, gastric tissue was sent for histopathological examination. Results: The combination of quercetin with misoprostol resulted in a comparable effect to esomeprazole regarding the inhibitory effect on gastric lesions, ulcer index, and free and total acidity. Moreover, this combination significantly decreased the level of LDH with a nonsignificant decrease in the IL-6 level. Esomeprazole and the combination group restored the level of catalase and quercetin alone and in the combination group elevated the level of GSH. Additionally, remarkable protection appeared in the pathological findings, especially in the group treated with quercetin and misoprostol. Conclusion: This study clearly revealed the gastroprotective effect produced by combining quercetin with misoprostol by decreasing ulcer area and index, restoring antioxidant enzyme levels, and ameliorating inflammation. These findings suggest the use of this combination in a clinical setting. Cite this article as: Ahmed ZA. Gastroprotective effect of quercetin and misoprostol in ethanol-induced gastric ulcer in rats. Turk J Gastroenterol. 2024;35(11):822-830.